The yes brain : how to cultivate courage, curiosity, and resilience in your child - Siegel, Daniel J., 1957-; Bryson, Tina Payne (Bantam, 2018)
"From the authors of The Whole-Brain Child and No-Drama Discipline, an indispensable guide to unlocking your child's innate capacity for resilience, compassion, and creativity. When facing challenges, unpleasant tasks, and contentious issues such as homework, screen time, food choices, and bedtime, children often act out or shut down, responding with reactivity instead of receptivity. This is what New York Times bestselling authors Daniel J. Siegel and Tina Payne Bryson call a No Brain response. But our kids can be taught to approach life with openness and curiosity. Parents can foster their children's ability to say yes to the world and welcome all that life has to offer, even during difficult times. This is what it means to cultivate a Yes Brain. When kids work from a Yes Brain, they're more willing to take chances and explore. They're more curious and imaginative, less worried about making mistakes. They're better at relationships and more flexible and resilient when it comes to handling adversity and big feelings. They work from a clear internal compass that directs their decisions, as well as the way they treat others. Guided by their Yes Brain, they become more open, creative, and resilient. In The Yes Brain, the authors give parents skills, scripts, ideas, and activities to bring kids of all ages into the overwhelmingly beneficial "yes" state. You'll learn the four fundamentals of the Yes Brain--balance, resilience, insight, and empathy--and how to strengthen them the key to knowing when kids need a gentle push out of a comfort zone vs. needing the "cushion" of safety and familiarity strategies for navigating away from negative behavioral and emotional states (aggression and withdrawal) and expanding your child's capacity for positivity With inspirational anecdotes, fun and helpful illustrations, and a handy Yes Brain Refrigerator Sheet to keep your family on point, The Yes Brain is an essential tool for nurturing positive potential and keeping your child's inner spark glowing and growing strong--and gifting your children with a life of rich relational connections, meaningful interactions with the world, and emotional equanimity. "Easily assimilated and informative, the book will help adults enable children to lead physically and emotionally satisfying and well-rounded lives filled with purpose and meaningful relationships. Edifying, easy-to-understand scientific research that shows the benefits that accrue when a child is encouraged to be inquisitive, spirited, and intrepid."--Kirkus Reviews "In today's busy, competitive culture, allowing our children the space to be themselves is more important than ever. This book provides an escape hatch from the high-stakes mindset."--Vicki Abeles, producer and co-director, The Race to Nowhere and Beyond Measure"--